(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2023)
Education is a necessity for every individual. The level of education is the main thing in advancing the quality of education. However, there are still difficulties experienced by some people in obtaining education, especially for those who are minorities. This study aims to discuss the right to obtain religious education for adherents of the belief in Indonesia. This study uses a qualitative approach with a discussion using a normative legal approach and data collection through literature study. The results and discussion of this research show that the state as the authority that runs the government based on the constitution has the responsibility to educate the nation’s life as stated in the preamble to the 1945 Constitution of the Republic of Indonesia in paragraph four, in the national education system there is a content of religious education that must be held in educational units, including participants adherents of the belief students who have formal education. This study concludes that religious education is a problem for students who adherents of the belief before the issuance of Permendikbud No. 27 of 2016 until it was published, as a legal protection for adherents of the belief, the regulation has not yet been fully realized.